Course review system - Shailaja, Maddala (Kansas State University, 2015)
The Course Review System (CRS) application reviews courses and their feedbacks, thereby providing a platform to learn about the courses being offered at Kansas State University (KSU) before enrollment. This can help current and also prospective students who are planning to enroll in courses at KSU to form an idea about the courses being offered at KSU. For the CRS application graduate and undergraduate level courses from 16 departments at KSU were included. Users can rate a course on a scale of 1 to 5 in three categories namely: Difficulty, Grading, and Learning Curve. Statistical analysis was used to display the top 10 courses in each department for each rating category. A recommendation feature which recommends courses to users based on the courses they are currently viewing was added to provide users with recommendations. Users could post their reviews and comments in the comments section. In addition to this we also have a ‘Questions and Answers’ section allowed users to ask questions and any interested user could answer them in that forum. Dimensional Research conducted a survey about the impact of opting courses via online reviews, in which 88% of respondents were influenced by online course reviews when selecting an online course [17]. In addition to the survey however, rational thinking suggests that obtaining an idea about a course involves reading through the experiences of actual users before deciding to select a course. Therefore, the proliferation of various review websites, including software application reviews, plays a major role. Reviews and ratings of a course provides users with an idea about the course they intend to take up and also helps in effectively planning out coursework for the semester. As users are looking for information to help them choose the most suitable course for their requirements course reviews are playing a larger role than they were in the past. It also helps students to make smart choices in laying out a flow chart for their program. The CRS application was a perfect platform for students to know everything they need to know about courses before they enroll.
Keywords: Review system; Computer Science (0984)